2017
DOI: 10.1111/mms.12400
|View full text |Cite
|
Sign up to set email alerts
|

Molting phenology of the Pacific harbor seal (Phoca vitulina richardii) on two islands off the Baja California Peninsula, Mexico

Abstract: We document and compare the annual molt of the Pacific harbor seal (Phoca vitulina richardii) on two islands off the west coast of the Baja California Peninsula that are the northern and southern extremes of its distribution in Mexico. During 2014, observations were made from March to July on Todos Santos Island (northern extreme) and from January to June on San Roque Island (southern extreme). On Todos Santos, the premolt lasted 15 wk (March–June) and the molt 12 wk (April–July). On San Roque, the premolt las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Previous studies reported late April as an optimal period for finding the highest number of individuals on land on San Roque Island (Tapia‐Harris et al . ), which coincides with the results of this study. In contrast, for Todos Santos Island, previous studies suggested early May as optimal for finding the highest aggregation of individuals on land (Fernández‐Martín et al .…”
Section: Statistical Summary Of the Generalized Additive Models For Psupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies reported late April as an optimal period for finding the highest number of individuals on land on San Roque Island (Tapia‐Harris et al . ), which coincides with the results of this study. In contrast, for Todos Santos Island, previous studies suggested early May as optimal for finding the highest aggregation of individuals on land (Fernández‐Martín et al .…”
Section: Statistical Summary Of the Generalized Additive Models For Psupporting
confidence: 93%
“…, Tapia‐Harris et al . ); however, the results obtained by this study point to early June as the main aggregation peak for this island. In conclusion, these results suggest that future counts for abundance estimations should be performed during the last days of April in the southern colonies near San Roque Island (including Asuncion, Natividad, and Cedros Islands, as well as the San Benito Archipelago) and during the first days of June in the northern colonies near Todos Santos Island (including Coronado, San Martín, and San Jerónimo Islands).…”
Section: Statistical Summary Of the Generalized Additive Models For Pcontrasting
confidence: 75%
See 1 more Smart Citation
“…The coordinates of the specific beaches where samples were collected are available in the metadata of the sequencing project in the database repository. Samples were collected during the molting season, when the highest numbers of individuals haul out [30] tending to remain on shore for many hours [31]. Each sample was collected individually using a disposable sterilized spatula.…”
Section: Methodsmentioning
confidence: 99%
“…Phenological shifts in life-history events, including breeding [37][38][39], pupping [40] and moulting [41] have been reported in many seal species. Many species of seal are known to undergo delayed implantation, or embryonic diapause [42][43][44], in common with other large carnivore species [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%